Composite bioscore is superior to routine biomarkers and established scoring systems in predicting mortality in adult critically ill patients with secondary sepsis - Rondović Goran; Šurbatović Maja; Đorđević Dragan; Stanojević Ivan; Zeba Snježana; Udovičić Ivo; Đukić Snežana; Erić Stevan; Šarac Momir; Vojvodić Danilo (Vojnosanitetski Pregled)
Background/Aim. Sepsis represents a significant global burden, with an estimated 48.9 million cases and 11.0 million sepsis-related deaths recently recorded worldwide. The aim of this observational study was to assess a prognostic value of some readily available routine biomarkers: presepsin, procalcitonin, C-reactive protein (CRP), white blood cell (WBC) count, platelet count, mean platelet volume (MPV), and lactate, as well as their combination regarding the outcome in a cohort of critically ill adult patients with secondary sepsis. Methods. A total of 86 critically ill patients with secondary sepsis due to peritonitis, pancreatitis, and severe trauma, admitted to the surgical intensive care unit, were enrolled in this prospective study. Blood samples for biomarker analysis were collected in three time points: on admission (the 1st day) and on the 3rd, and 5th day after admission. The Sequential Organ Failure Assessment (SOFA) score, the Simplified Acute Physiology Score (SAPS) II, and the Acute Physiology and Chronic Health Evaluation (APACHE) II score were calculated and recorded within the first 24 hours after admission (1st day). SOFA and SAPS II scores were recorded daily. The primary end-point was hospital mortality. Results. Values of each applied score were expectedly significantly higher in non-survivors in all time points. Regarding investigated parameters, only presepsin levels were significantly higher in non-survivors in all time points; MPV levels on the 3rd and 5th day; serum lactate levels on the 3rd day; CRP levels and WBC count on the 5th day. Clinical accuracy of parameters in predicting lethal outcomes was investigated in all time points. On the 1st day, apart from all three scores, only presepsin demonstrated statistically significant discriminative power regarding outcome (AUC of 0.670). Apart from SAPS II and SOFA score, on the 3rd day presepsin, MPV, and lactate (AUCs of 0.716, 0.667, and 0.642, respectively) and on the 5th day presepsin, MPV, CRP, and WBC count (AUCs of 0.790, 0.681, 0.643 and 0.654, respectively) were good predictors of the lethal outcome. Composite bioscore (presepsin, MVP, and lactate) on the 3rd day had the highest AUC of 0.820 in comparison with individual scores and parameters. The independent predictor of the lethal outcome on the 1st day was presepsin (p < 0.05) and on the 3rd day MPV (p < 0.01). Conclusion. Composite bioscore is superior to routine biomarkers and established scoring systems in predicting mortality in adult critically ill patients with secondary sepsis.